ASSESSING NUTRITIONAL STATUS OF SCHOOL CHILDREN OF A SINDH REGION ON SOCIO-DEMOGRAPHIC INDICATORS - Aijaz Ahmed Noonari; Rukhsana Khan; Mudassar Mushtaq Jawad Abbasi et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT: BACKGROUND: Malnutrition is public health issue of school-age children. Inadequacy, availability, poor quality and lack of knowledge of balanced diet are major causes of under-nutrition. Current study aimed to assess the nutritional status and associated factors among primary school children of Thul-Town, Jacobabad, and Sindh. METHODS: A cross-sectional study conducted on 210 children, equally divided boys and girls selected by simple random method. Anthropometrics measures, socio-demographic characteristics data were collected using pretested questionnaire. Using WHO-reference-2007, height, BMI and weight-for-age were measured for stunting, wasting and underweight respectively and BMI-for-age for overweight and obesity. Data analysis was done by using SPSS-21, WHO AnthroPlus and NutriSsurvey softwares. Dietary data was collected through a 24-hour recall and FFQ to determinefood choice and portion size. Chi-square test at 95% conﬁdence interval (CI) was used to quantify independent variables of nutritional indices. RESULTS: Prevalence of stunting, wasting, underweight, overweight and obese were found 10%, 14%, 11%, 0.5% and 0.5% respectively. Stunting was signiﬁcantly associated with family size (p0.037), monthly income (p-0.038) and pocket money (p-0.007). Wasting was signiﬁcantly associated with decision making power (p-0.000), mother’s education (p-0.000) and occupation (p-0.000). Underweight was associated with decision making power (p-0.002) and vit-C (p-0.028). Out of total children 79% were taking inadequate food servings. Generally it was pointed out that 71% children were taking insuﬃcient of all nutrients as per RDA. CONCLUSIONS: Low stunting, high wasting and medium underweight observed. Girls were more undernourished by all indices than boys. However, family size, monthly income, decision making power, education and occupation of mother were found signiﬁcantly associated with nutritional status of children.